(untitled) (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2022)
Tetralogy of Fallot is a common cyanotic congenital heart disease. Early surgery treatment gives patients a chance to have normal physical and mental health due to preventing complications of cyanosis and even death as a natural history of tetralogy of Fallot. This study aimed to show short-term outcomes (including the time of postoperative hospital stay and 30 days after discharge) of tetralogy of Fallot complete repair at the Department of Pediatric Cardiac Surgery, Cho Ray Hospital. A retrospective study was performed on the data of medical documents of 38 patients, who underwent complete repair for tetralogy of Fallot with full sternotomy and cardiopulmonary bypass from March 2017 to December 2019, following a collection form. The results showed the average age and weight were 33.89±13.02 months and 11.77±2.48 kg. The cardiopulmonary bypass time was 147.74±12.48 mins, the aortic cross-clamp time 104.84±9.73 mins, the mechanical ventilation time 31.14±10.75 hours, the duration of stay in the intensive care unit 58.03±13.56 hours, the postoperative hospital stay time 10.12±1.5 days, and the mortality rate 2.6%. The study concludes that the short-term surgical outcome of complete repair for tetralogy of Fallot in lightweight children is safe and effective with a low mortality rate.